C-Reactive Protein Levels and Gadolinium-Enhancing Lesions Are Associated With the Degree of Depressive Symptoms in Newly Diagnosed Multiple Sclerosis - Yalachkov, Yavor; Anschuetz, Victoria; Jakob, Jasmin; Schaller-Paule, Martin A.; Schaefer, Jan Hendrik; Reilaender, Annemarie; Friedauer, Lucie; Behrens, Marion; Foerch, Christian (Frontiers in Neurology, 2021)
Background: Inflammation is essential for the pathogenesis of multiple sclerosis (MS). While the immune system contribution to the development of neurological symptoms has been intensively studied, inflammatory biomarkers for mental symptoms such as depression are poorly understood in the context of MS. Here, we test if depression correlates with peripheral and central inflammation markers in MS patients as soon as the diagnosis is established. Methods: Forty-four patients were newly diagnosed with relapsing-remitting MS, primary progressive MS or clinically isolated syndrome. Age, gender, EDSS, C-reactive protein (CRP), albumin, white blood cells count in cerebrospinal fluid (CSF WBC), presence of gadolinium enhanced lesions (GE) on T1-weighted images and total number of typical MS lesion locations were included in linear regression models to predict Beck Depression Inventory (BDI) score and the depression dimension of the Symptoms Checklist 90-Revised (SCL90RD). Results: CRP elevation and GE predicted significantly BDI (CRP: p = 0.007; GE: p = 0.019) and SCL90RD (CRP: p = 0.004; GE: p = 0.049). The combination of both factors resulted in more pronounced depressive symptoms (p = 0.04). CSF WBC and EDSS as well as the other variables were not correlated with depressive symptoms. Conclusions: CRP elevation and GE are associated with depressive symptoms in newly diagnosed MS patients. These markers can be used to identify MS patients exhibiting a high risk for the development of depressive symptoms in early phases of the disease.